Rancang Bangun Pembangkit Listrik Tenaga Gelombang Laut Menggunakan Sistem Oscillating Water Column - Siti Rohmaniatul Adafiah; Artdhita Fajar Pratiwi; Saepul Rahmat (Infotekmesin, 2021)
Ocean wave power plant is one of the plants that uses sea waves as the main energy. Although the amount of energy is abundant, in Indonesia the use of sea waves as electricity generators is still small. This is due to the lack of human resources to manage the wave energy of sea water. Many research studies on the Oscillating Water Column have been carried out, but it is only limited to a potential or feasibility study to be installed on the coast. Therefore, the focus of this research is to design a sea wave power plant with an oscillating water column system. The working process of the tool begins by adjusting the pwm to drive the motor power window which is connected to the wave arm. When the wave arm moves back and forth, it will produce artificial ocean waves. Artificial waves in the chamber produce compressed air, the air produced is used to rotate the turbine blades that have been connected to the generator to produce electrical energy. The greatest voltage and current is obtained when the wind speed reaches 7.7 m / s and the largest pulley rotating speed reaches 31,9 rpm at the 17 cm water level, which is 3.03 V DC and 6,07 mA. The test results prove that the potential of water waves can be used to generate electricity The development of the capacity of ocean wave power plants can be done by changing the dimensions of the turbines and increasing the capacity of the generator.